Sustainable Development Goals-Based Digital Comics for Enhancing Primary Students’ English Reading Literacy: A Systematic Literature Review - I Komang Agus Dio Aditya; Ni Komang Arie Suwastini; Ni Wayan Surya Mahayanti (Universitas Pendidikan Ganesha, 2026)
Reading literacy remains a persistent challenge in primary education, particularly because students often show low reading interest and limited engagement with conventional reading materials. This study aims to examine the characteristics, advantages, and challenges of Sustainable Development Goals (SDGs)-based digital comics for students’ English literacy in primary schools. A library research design was employed by adapting George’s research procedure, which involved topic determination, research question formulation, source selection, article screening, data reduction, synthesis, and reporting. Twenty-nine articles from reputable national and international indexed journals were analyzed thematically. The findings reveal that SDG-based digital comics have three main characteristics: visual attractiveness, ease of use and access, and relevance to 21st-century learning. The reviewed studies also show that this medium supports vocabulary mastery, reading comprehension, communication skills, writing skills, learning outcomes, literacy competence, and digital literacy. However, several challenges were identified, including time-consuming preparation, limited teacher knowledge of technology and SDGs, and development or adaptation costs. This study implies that SDG-based digital comics can serve as engaging, contextual, and sustainability-oriented literacy media for primary school students.